SEMANTIC WAVES IN THE TEACHING OF PORTUGUESE AS AN ADDITIONAL LANGUAGE: SEMANTIC GRAVITY AND SEMANTIC DENSITY IN THE CONSTRUCTION OF KNOWLEDGE - Silva, Antonio Marcio (2023)
Teaching Portuguese as an Additional Language in an academic context requires contemplating uses of this language in oral and written productions that involve different degrees of abstraction and semantic complexity. These practices are interconnected by two aspects: by the way in which practical, horizontal and everyday knowledge prevails in high school and theoretical, vertical, and abstract knowledge in higher education; and also because it is an additional language. These challenges lie in the semantic dimension that conceives these practices as semantic waves whose organizing principles comprise semantic gravity (SG) and semantic density (SD) (MATON, 2013; 2020). The aim of this study is to discuss how semantic waves can be evidenced in a Portuguese as an Additional Language course organized into topics, offered to first- year undergraduate students at a British university. The analysis focuses on samples of the teaching materials and some tasks completed by learners to demonstrate how knowledge initially characterized by strong semantic density is “unpacked” (MATON, 2020) through different examples and practical uses. The contribution concerns the benefit of taking semantic waves into account when planning an additional language course, since most studies focus on other areas of knowledge, but little on the teaching of languages, especially Portuguese as an Additional Language.